Preparation method of bio-based high-transparency and high-impact PVB (Polyvinyl Butyral) adhesive film
By using squid bone nanofiber and triethylene glycol diisocitate in PVB film, combined with the process of twin screw extruder and caster, the shortcomings of the existing PVB film in high transparency and high impact resistance are solved, and a PVB film with high transparency, high tensile strength and good optical performance are achieved.
Patent Information
- Application Number
- CN202411805759.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
The existing PVB films have shortcomings in high transparency and high impact resistance, which are difficult to meet the demand for high-performance laminated glass in modern architectural and automotive fields.
Squid bone nanofibers were used as filler material and triethylene glycol diisocitate as plasticizer to prepare a high-transparent and high-impact PVB film through a combined process of twin-screw extruder and caster.
The high transparency and high tensile strength of the PVB film are achieved, the light transmittance remains above 85%, and the tensile strength is increased by 28.3%, while maintaining good optical and mechanical properties.
Smart Images

Figure CN119614105A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of PVB films, and in particular relates to a method for preparing a bio-based highly transparent and highly impact-resistant PVB film. Background Art
[0002] PVB film has good adhesion to inorganic glass and is mainly used for laminated glass, which is a layer of PVB film with polyvinyl butyral as the main component sandwiched between two pieces of glass. PVB laminated glass has multiple functions such as safety, heat preservation, noise control and UV isolation. Especially when subjected to strong external impact, the PVB film can absorb the impact energy and firmly adhere to the glass fragments so that the glass fragments will not fall and hurt people. It is widely used in high-rise buildings, automobiles, aviation, navigation and other fields. Those skilled in the art are in urgent need of developing a method for preparing a bio-based high-transparency and high-impact PVB film to meet the existing application market and performance requirements. Summary of the invention
[0003] In view of this, the present invention provides a method for preparing a bio-based highly transparent and high-impact PVB film.
[0004] Furthermore, the method comprises the following steps: mixing raw materials PVB resin powder, plasticizer and squid bone nanofiber evenly according to weight ratio, adding the raw materials to a twin-screw extruder with a slit die to extrude a sheet; after cooling by a cooling roller, stretching the sheet through a melt casting machine to form a film, and then measuring thickness, pulling and flattening, trimming and winding to obtain a highly transparent and high-impact PVB film.
[0005] Furthermore, the plasticizer is triethylene glycol diisooctanoate.
[0006] Furthermore, the mass ratio of the PVB resin, plasticizer and squid bone nanofiber in the first step is 72.5:27.5:0.3625-0.725.
[0007] Furthermore, the viscosity of the PVB resin powder is 180-200 mPa·s.
[0008] Furthermore, the squid bone nanofiber is prepared by alkalizing and purifying the strips of squid bone, deproteinizing, washing and neutralizing, crushing, TEMPO oxidation, and high-pressure homogenizer treatment to obtain a colorless and transparent squid bone nanofiber water suspension, freeze-drying with a freeze dryer, and crushing to obtain squid bone nanofiber for standby use. The preparation method is mechanical crushing, Tempo oxidation, and then high-pressure homogenization to obtain squid bone nanofiber white powder, with a single fiber diameter of 5-15nm and an aspect ratio of 400-500.
[0009] Furthermore, the temperature parameters of each section of the melting twin-screw extruder are set to 150° C., 155° C., 160° C., and 155° C., and the extrusion speed is 100 r / min.
[0010] Furthermore, the temperature parameters of each section of the melt casting machine are set to 130°C, 135°C, 140°C, 135°C, and the drafting speed is 100r / min. The temperature parameters of each section of the twin-screw extruder are set to 130°C, 135°C, 140°C, 135°C, the screw speed is 65-70r / min, and the extrusion speed is 100r / min.
[0011] 2,2,6,6-Tetramethylpiperidinyl oxide, abbreviated as TEMPO (2,2,6,6-tetramethylpiperidin-1-oxyl free radical), is a piperidine nitroxide free radical.
[0012] Beneficial effects of the present invention: The preparation method of the high-transparency and high-impact PVB film disclosed in the present invention is filled with transparent nanofibers prepared from squid bones, which are food waste, and plasticized with triethylene glycol diisooctanoate; squid bone β-chitin, because its crystal plane spacing is larger than that of conventional shrimp and crab shell α-chitin and cotton straw-based cellulose, no longer presents the rigid characteristics of conventional nano-biomass, but shows the advantages of high aspect ratio, mechanical flexibility, and optical transparency, and its sugar ring and acetylamino group have good compatibility with PVB substrate, when the amount of squid bone nanofiber added is less than 1wt%, the light transmittance of the prepared PVB film is still above 85%, and when the amount of squid bone nanofiber added is 0.5wt%, the tensile strength can be increased to 18.22±0.55MPa, which is 28.3% higher than that of pure PVB. Through the simple processing technology of twin-screw melt extrusion combined with melt casting, a modified PVB film with good optical properties and significantly improved tensile strength is obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 is a SEM photograph of high pressure homogenized squid bone nanofiber (NCT) in Example 1; Figure 2 The PVB film prepared by the solution method in Comparative Example 1; Figure 3 The following are photos of PVB / NCT composite film samples at various ratios, including (a) pure PVB; (b) 0.5 wt%; (c) 1 wt%; (d) composite film photos with 1.5 wt% NCT addition. Figure 4 This is the effect of squid bone nanofiber addition on the transmittance of the sample; Figure 5 is a stress-strain curve diagram of the PVB / NCT composite film at various ratios in Example 1; Figure 6 The morphology of the PVB film extruded at the die head temperature in Example 1, where (a) 130°C; (b) 135°C; (c) 140°C; (d) 150°C; Figure 7It is composite laminated glass and broken laminated glass; Figure 8 This is the front view of the production line of Example 2; Fig. 9 This is a top view of the production line of Example 2. DETAILED DESCRIPTION
[0014] Raw materials: PVBWW-A-30 came from Anhui Wanwei High-tech Materials Co., Ltd.; triethylene glycol diethylhexanoate WW-3G8 came from Anhui Wanwei High-tech Materials Co., Ltd.; TEMPO reagent analytical grade Aladdin Chemical Reagent Co., Ltd.; sodium hydroxide analytical grade Chengdu Cologne Chemical Co., Ltd.; sodium bromide analytical grade Shanghai MacLean Biochemical Technology Co., Ltd.; sodium hypochlorite analytical grade Aladdin Chemical Reagent Co., Ltd. The preparation of squid bone nanofibers with a single fiber diameter of 5-15 nm refers to the following high-pressure homogenized squid bone nanofibers; Example 1 Preparation of high-pressure homogenized squid bone nanofiber freeze-dried powder (NCT): by weight, crush 1 part of strip squid bones and place them in deionized water for soaking and cleaning to wash away surface impurities, then place them in a 2% NaOH solution by mass and heat and clean them at 80°C for 12 hours according to a bath ratio of 1:4, take them out and mechanically crush them, dissolve 0.1 part of TEMPO2,2,6,6-tetramethylpiperidine-1-oxyl free radical and 4.5 parts of sodium chlorite and 400 parts of water in a beaker, stir at room temperature at 1000r / min for 4 hours, then stir and react at 50°C for 48 hours, cool to room temperature, and then perform high-pressure homogenization at 100MPa for 10 cycles, and then place them in a freeze dryer with a cold trap temperature of -50°C and freeze-dry for 48 hours to obtain squid bone nanofiber freeze-dried powder (NCT). Equipment: Twin-screw extruder GJZS-20 Wuhan Ruiming Experimental Instrument Manufacturing Co., Ltd.; experimental air-cooled conveyor SFS-120 Wuhan Ruiming Experimental Instrument Manufacturing Co., Ltd.; electric constant temperature blast drying oven DHG-9140A Shanghai Sanfa Scientific Instrument Co., Ltd.; constant temperature heating magnetic stirrer DF-101S Wuhan Delixiang Instrument Equipment Co., Ltd.; cast film unidirectional stretching machine SDLY-200 Wuhan Ruiming Experimental Instrument Manufacturing Co., Ltd.; program-controlled tablet press SY-6210-B Guangdong Shiyan Precision Instrument Co., Ltd.; vacuum freeze dryer FD-1A-50+ Boyikang (Beijing) Instrument Co., Ltd.; electronic universal testing machine UTM24059 Shenzhen Sansi Zongheng Technology Co., Ltd.; haze meter YH1200 Guangdong Sanenshi Intelligent Technology Co., Ltd. Example 1
[0015] After mixing powdered PVB resin, plasticizer 3G8 and squid bone nanofiber freeze-dried powder (NCT) in a certain proportion, knead in a torque rheometer for 5 minutes at a temperature of 140°C. Too high a temperature will cause yellowing of PVB and volatilization of plasticizer. Then, the mixed and plasticized PVB is pressed into a film using a vacuum sheet press.
[0016] The production of PVB cast film was simulated using a laboratory micro twin-screw extruder and a micro cast film unidirectional stretching machine. The parameters such as the temperature of each section of the extruder, the die head temperature, the casting roll temperature, the rotation speed of each roller and the trimming loss rate during the production process were explored so that the process parameters can be determined through enlarged experiments during process design. Calculated by weight fraction, 72.5 parts of PVB resin powder, 27.5 parts of plasticizer, and based on 100% of the weight of the PVB resin powder, the addition amount of squid bone nanofiber freeze-dried powder was 0.5wt%, 1wt% and 1.5wt% of the dry weight of the PVB resin powder.
[0017] Experimental results and discussion: 1. Light transmission performance analysis Figure 3 The following are the samples of pure PVB, NCT with an addition amount of 0.5wt%, 1wt%, and 1.5wt% and the samples of NCT with an addition amount of 0.5wt%, 1wt%, and 1.5wt% respectively. After adding squid bone nanofiber NCT, NCT as a dispersed phase may scatter or absorb light, resulting in a decrease in the light transmittance of the sample. Figure 4 As can be seen from Table 1, the transmittance of pure PVB can reach more than 90%. After adding 0.5wt% NCT, the transmittance of the composite film dropped to (87.22±0.99)%. After adding 1wt% NCT, the transmittance continued to drop to (86.06±0.52)%. Although the transmittance has dropped to a certain extent compared with the pure PVB film, it generally meets the standard of transmittance ≥85%. However, after adding 1.5wt% NCT to the PVB resin, the transmittance of the composite film dropped sharply to (81.11±1.00)%, and the transmittance was lower than the technical requirements of the intermediate film. Therefore, the subsequent experiments controlled the addition of NCT below 1wt%. Figure 3 These are the PVB / NCT composite film samples at various ratios, including (a) pure PVB, (b) 0.5wt%, (c) 1wt%, and (d) 1.5wt% NCT added composite films. Figure 4 It is the effect of NCT addition on the transmittance of the sample.
[0018] Table 1 Transmittance of PVB / NCT composite films at various ratios
[0019] 2. Tensile performance analysis Figure 5These are the stress-strain curves of pure PVB, composite film with 0.5% NCT added by solution method, composite film with 1% NCT added, and composite film with 1% NCT added by melt method. From Table 3.1, we can see that the tensile strength of pure PVB is (12.64±1.67) MPa. After adding NCT, the tensile strength of the samples all increased to a certain extent. Because in the previous transmittance test, it was found that after adding 1.5wt% NCT, the transmittance of the prepared sample was lower than the 85% transmittance in the standard, so the tensile performance test was no longer continued. For the composite film prepared by the solution method, it was found that when the NCT addition amount was 0.5wt%, the tensile strength increased to (16.22±0.55) MPa, which was 28.3% higher than that of pure PVB. When the NCT addition amount was 1wt%, the tensile strength increased to (16.95±1.86) MPa, which was 34.1% higher than that of pure PVB. At the same time, in order to compare the tensile properties of the samples prepared by the solution method and the melt method, the sample prepared by the melt method with 1wt% NCT added was also measured, and its tensile strength was found to be (17.12±2.18)MPa, which was not much different from the sample with the same ratio prepared by the solution method. Therefore, it can be concluded that with the increase of the amount of NCT added, the tensile strength of the PVB / NCT composite film also increases, and different processing methods (solution blending method, melt blending method) have almost no effect on the tensile strength of the prepared sample. The possible reason is that the nanoscale size and high surface area of the squid bone nanofibers enable it to have a larger contact area with the PVB resin matrix, thereby enhancing the adhesion between them. When subjected to tensile external force, the squid bone nanofibers will be arranged in an orderly manner and absorb the external force on the material, thereby achieving the effect of improving the tensile strength. At the same time, when the amount of NCT added is less than 1wt%, although the addition of NCT will slightly reduce the elongation at break of the sample, it is still above 200%, which meets the requirements of the standard. From an economic perspective, when the NCT addition amount is 0.5wt%, its tensile properties can be significantly improved. Therefore, only 0.5wt% of NCT needs to be added in the subsequent cast film formula design. Figure 5 1 is the stress-strain curve of PVB / NCT composite film under various ratios. Table 2 is the tensile strength and elongation at break of PVB / NCT composite film under various ratios.
[0020] Table 2 Tensile strength and elongation at break of PVB / NCT composite films at various ratios
[0021] 3. Process Conditions Analysis (1) Die head temperature Due to the different rheological properties of PVB resin at different temperatures, the surface morphology of the extruded film will be different. When the extrusion temperature is high, the viscosity of PVB is low and the fluidity is good, so the surface will be smoother. When the temperature is low, the fluidity of PVB is poor. Under the force of the die, it will cause traces of poor flow on the surface. By changing the temperature of each section and die of the extruder, the change of the surface morphology of the extruded film was observed. When the die temperature of the extruder is 120℃, the surface of the extruded PVB film is very rough, and some PVB is not completely plasticized; when the die temperature is 130℃ and 135℃, the surface has obvious patterns; when the die temperature is 140℃ and 150℃, the surface is relatively smooth and flat. When the die temperature is greater than 160℃, the viscosity of PVB is too low and the fluidity is too good, so the extrusion pressure cannot be reached, and the PVB film cannot be extruded at all.
[0022] When used as the middle layer of laminated glass, if the surface of the PVB film is too flat, it is easy to trap air during the lamination process, resulting in bubbles in the laminated glass, thus affecting the quality of the laminated glass. The uneven surface of the middle layer makes it easier to exhaust. Therefore, the temperature of the extruder die should be controlled between 130~140℃. Figure 6 The following are the morphology photos of PVB films extruded at die head temperatures of (a) 130℃, (b) 135℃, (c) 140℃, and (d) 150℃. Table 3 shows the effect of extrusion temperature on the surface morphology of the film.
[0023] Table 3 Effect of extrusion temperature on film surface morphology
[0024] (2) Casting roll temperature and roll speed The micro cast film unidirectional stretching machine used in the experiment can perform a unidirectional stretching effect on the cast film by adjusting the roller speed of the front and rear rollers. Through the reference of relevant literature and books and the verification of experiments, when the ratio of the front and rear roller speeds is 1:1.2, a cast film with uniform thickness can be obtained, and it will not break during the stretching process. In addition to the influence of the roller speed, the temperature of the cast roller will also have an impact on it. If the roller temperature is too low, the thickness of the cast film obtained is uneven; if the roller temperature is too high, the PVB film will easily break during the casting process. Through the casting test of PVB film at different roller temperatures, it was found that when the roller temperature was 100°C, a thick and uniform cast film could be obtained without breaking.
[0025] (3) Laminated glass composite effect Since there is no special equipment for compounding laminated glass, a vacuum press is used in the laboratory to simulate the process of compounding laminated glass to preliminarily test whether the bonding between the PVB / NCT composite film and the glass is good. Through experiments, it is found that when the hot pressing pressure of the vacuum press exceeds 2MPa, the glass is easily crushed. A smaller compounding pressure cannot achieve a good compounding effect. Under the operation of the vacuum press, there are more defects around the laminated glass after compounding, which may be due to the fact that the pressure is not enough to make the PVB interlayer flow and fill the entire laminated glass. This should have a relatively large impact on the quality of the laminated glass.
[0026] See Figure 7 , and then used a small hammer to knock on the laminated glass. It was found that after the glass was broken, in addition to a large amount of glass shattered in the center, there were radial cracks around it, and most of the glass was still stuck to the PVB middle layer.
[0027] Comparative Example 1 Powdered PVB resin was added to ethanol to prepare a PVB ethanol solution with a concentration of 10wt%. Plasticizer 3G8 (the ratio was determined to be 72.5 parts of PVB powder and 27.5 parts of plasticizer, and the ratio remained unchanged in subsequent experiments) and NCT replaced with ethanol (the solid content was 0.5% and 1% of the mass of PVB resin, respectively) were added in a certain proportion, mixed evenly, and then placed in an ultrasonic cleaner for ultrasonic dispersion. After that, the mixed solution was poured into a glass dish of a certain size and placed in a 50°C oven to evaporate the solvent. The resulting film was thin and had bubbles, so a vacuum tablet press was needed to press it into a film with uniform thickness and no bubbles. The vacuum tablet press was set at a temperature of 140°C, and was pre-pressed at 2MPa for 2min for exhaust treatment. Then the pressure was increased to 10MPa and the pressure was maintained for 5min. If the temperature of the tablet press was too high or the time was too long, the obtained PVB film would turn yellow, affecting the quality of the film. Figure 2 This is a photo of PVB film prepared by solution method. Example 2
[0028] First, the raw materials PVB resin powder, plasticizer 3G8, and squid bone nanofiber are mixed evenly according to the proportion, and then added to a twin-screw extruder with a slit die to extrude the sheet. After cooling by a cooling roller, it is cast into a film by a casting machine, and then it is measured for thickness, flattened by pulling, trimmed, and rolled up to obtain a PVB cast film with consistent thickness and width. Figure 8 This is the main view of the production line. Fig. 9 This is a top view of the production line.
[0029] The film-grade PVB resin powder of raw material WW-B-10 is white or slightly yellow powder, with a hydroxyl content of 17% to 20%, a volatile matter of ≤2.0%, a viscosity of 180 to 200 mPa·S, and a bulk density of ≥0.2 g / cm3 , melt index 0.80~2.20g / 10min. SRL-Z800 mixer: total volume 800L, effective feed 320kg / pot, motor power 22kW, spindle speed 50r / min. GWP-95 extruder, screw diameter 180mm, aspect ratio L / D44:1, main power 250kW, screw speed 100r / min, extrusion volume 650kg / h. Temperature of each temperature zone of the extruder: temperature zone 1 130℃, 2nd zone 135℃, 3rd zone 140℃, die head 135℃. Die half width 180cm, material density 1.08g / cm 3 , die thickness 0.05cm, material non-Newtonian index n0.6. Roller diameter 600mm, line speed 15m / min. Feed ratio: PVB resin, plasticizer triethylene glycol diethylhexanoate, squid bone nanofiber mass ratio is 72.5:27.5:0.3625.
[0030] Note: According to the method specified in GB / T2918-2018, the state was conditioned for 6 hours at a temperature of 23°C and a relative humidity of 50%, and the test was carried out under this environment. The tensile performance test was carried out in accordance with GB / T1040.1-2018, type 5 specimens, and 5 specimens were selected for tensile performance test on a universal testing machine (UTM24059), and the tensile rate was set to 10mm / min. The initial distance between the two fixtures was 30mm, the specimen width was 4mm, and the thickness was 0.25mm. The transmittance test was carried out in accordance with GB / T2410-2008, and 5 specimens were selected for transmittance test on a haze meter (YH1200). For the same specimen, three places without impurities were selected for transmittance test. Laminated glass composite The PVB film is composited with two pieces of ordinary glass, stacked together in the form of glass-intermediate film layer-glass, and the excess film at the edge is cut off. The mixture was placed in a vacuum tablet press and vacuum hot pressed at 140°C and 1.5 MPa for 20 min.
Claims
1. A method for preparing a bio-based highly transparent and high-impact PVB film, characterized in that: The following steps are involved: The raw materials PVB resin powder, plasticizer and squid bone nanofiber are mixed evenly according to the weight ratio, and added into a twin-screw extruder with a slit die to extrude the sheet; after cooling by a cooling roller, it is melt-cast and stretched into a film by a casting machine, and then the film is measured in thickness, flattened by traction, trimmed and rolled to obtain a fully biodegradable, highly transparent and high-impact PVB film.
2. The method for preparing a highly transparent and high-impact PVB film according to claim 1, characterized in that: The plasticizer is triethylene glycol diisooctanoate.
3. The method for preparing the bio-based high-transparency and high-impact PVB film according to claim 1, characterized in that: The mass ratio of the PVB resin, the plasticizer and the squid bone nanofiber is 72.5:27.5:0.3625-0.
725.
4. The method for preparing the bio-based high-transparency and high-impact PVB film according to claim 1, characterized in that: The viscosity of the PVB resin powder is 180-200 mPa·s.
5. The method for preparing the bio-based high-transparency and high-impact PVB film according to claim 1, characterized in that: The squid bone nanofiber aqueous solution is transparent and colorless in appearance, does not aggregate after freeze-drying, has a single fiber diameter of 5-15 nm, and an aspect ratio of 400-500.
6. The method for preparing the bio-based high-transparency and high-impact PVB film according to claim 1, characterized in that: The temperature parameters of each section of the twin-screw extruder were set to 150°C, 155°C, 160°C, and 155°C, and the extrusion speed was 100 r / min.
7. The method for preparing the bio-based high-transparency and high-impact PVB film according to claim 1, characterized in that: The temperature parameters of each section of the melt casting machine were set to 130°C, 135°C, 140°C, and 135°C, and the drawing speed was 100r / min.